Industrıal Steel Structures in Hadımköy Regıon for the Perıod 2018-2023: Systemıc Solutıons For Changıng Needs (Architecture Image Studies, 2023)
In line with the building needs arising with the increase in industrialization in Hadımköy district, the tendency towards steel construction has increased significantly. The aim of this study is to reveal the necessity of building industrial buildings with steel construction in order to prevent disaster and soil problems in Hadımköy region. For this purpose, three factory examples from the Hadımköy region, which were partially or completely built with steel construction, were discussed. The evaluations made on these examples aim to qualitatively examine the hardware features of the construction in line with the changing needs of the industry. In this context, two buildings with different functions were evaluated and analyzed in terms of structural quality, flexibility, sustainability, durability and resistance to disasters. In line with the findings, it has been determined that the construction of industrial buildings in accordance with the changing needs of industrial buildings is provided by the use of steel construction system. The result of this study is an important reference in terms of preventing disasters and soil problems in the region by increasing the use of steel construction structures in regions with dense industrial buildings such as Hadımköy district.